Comparison of serum procalcitonin and interleukin-6 levels with CRP levels in the follow-up of antimicrobial treatment of patients with pyogenic and granulomatous vertebral osteomyelitis - Türkoğlu, Emine; Demirtürk, Neşe; Köken, Tülay; Korkmaz, Serhat; Yücel, Draylin (Journal of Surgery and Medicine, 2021)
Background/Aim: Infection of the intervertebral disc and adjacent vertebrae is called vertebral osteomyelitis (VO). This study aims to determine whether procalcitonin (PCT) and interleukin (IL)-6 markers are more valuable than white blood cells (WBC), C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) in the follow-up in patients with VO who were administered antibiotherapy. Methods: All adult patients with a diagnosis of VO were included in this prospective cohort study. The patients were divided into two groups as those with pyogenic and granulomatous VO. Serum WBC, CRP, ESH, PCT and IL-6 levels were measured at baseline, and the 2nd, 4th, 8th and 12th weeks of antibiotherapy. The changes in the laboratory parameters of the patients during follow-up were evaluated. Results: Of the 30 patients included in the study, there were 22 and 8 patients in the PVO and GVO groups, respectively. Baseline IL-6 measurement was above the reference in all patients, CRP was elevated in 96.6%, and PCT was increased in only one patient. Although there was a paradoxical increase in PCT values in the PVO group in the 2nd week compared to the pre-treatment values, a rapid decrease was observed in the 4th and 8th weeks. In the GVO group, the gradual decrease in PCT in parallel with the treatment response was considered to predict clinical improvement. IL-6 values decreased by 43.2% and 50% compared to baseline at the 4th and 8th weeks of treatment, respectively, in the PVO group. In the GVO group, a 50% reduction was detected in the 4th week of treatment compared to baseline. Conclusion: PCT and IL-6 biomarkers are valuable indicators in treatment follow-up. Although not statistically significant, the most stable decrease was observed in IL-6. Using IL-6 for the follow-up of the patients with VO may prevent long-term antibiotherapy.